Determination of the enantiomeric composition of amphetamine, methamphetamine and 3, 4‐methylendioxy‐N‐methylamphetamine (MDMA) in seized street drug samples from southern Germany. Issue 3 (1st July 2021) - Losacker, Moritz; Zörntlein, Siegfried; Schwarze, Bernd; Staudt, Svenja; Röhrich, Jörg; Hess, Cornelius
Abstract: Amphetamine ( speed ), methamphetamine ( crystal meth ), and 3, 4‐methylenedioxy‐N‐methylamphetamine (MDMA, ecstasy ) represent the most frequently abused amphetamine‐type stimulants (ATS). Differences in pharmacological potency and metabolism have been shown for the enantiomers of all three stimulants. Legal consequences in cases of drug possession may also differ according to the German law depending on the enantiomeric composition of the seized drug. Therefore, enantioselective monitoring of seized specimens is crucial for legal and forensic casework. Various kinds of samples of amphetamine ( n = 143), MDMA ( n = 94), and methamphetamine ( n = 528) that were seized in southern Germany in 2019 and 2020 were analyzed for their chiral composition using different chromatographic methods. Whereas all samples of amphetamine and MDMA were racemic mixtures, the chiral composition of the methamphetamine specimens was diverse. Although the vast majority ( n = 502) was present as (S)‐methamphetamine, also specimens containing pure (R)‐methamphetamine ( n = 7) were found. Furthermore, few samples ( n = 8) were of racemic nature or contained non‐racemic mixtures of both enantiomers ( n = 10). Because methamphetamine appears in varying enantiomeric compositions, any seizure should be analyzed using an enantioselective method. Amphetamine and MDMA, on the other hand, currently appear to be synthesized exclusively via racemic pathways and are not chirally purified. Nevertheless, regular monitoring of the chiral composition should be ensured. Abstract : Amphetamine, methamphetamine, and 3, 4‐methylendioxy‐ N ‐methylamphetamine (MDMA) exist in two enantiomeric forms and can be produced either in enantiopure form or as racemate. Seized street drug samples from southern Germany were analyzed using chiral liquid chromatography methods. Amphetamine and MDMA were present exclusively as racemate, whereas methamphetamine was mostly present in enantiopure (S)‐form, with a few exceptions.